Pregnancy-associated melanonychia striata. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2019)
Dark phototype and pregnancy are the only physiological conditions in which melanonychia striata can be observed; this can also be linked to numerous pathological conditions that must be excluded. Hyperpigmentation is common in pregnancy usually involving normally hyperpigmented areas – nipples and areolae, armpits, anus and perineum, friction areas –; it can also affect the linea alba which becomes nigra and associate with chloasma. Melanonychia striata is exceptional in the white pregnant woman, as showed by only two cases in the literature (1, 2). Alongside the hormonal factors, certainly important given the regression in puerperium, other factors are to be hypothesized – photoexposure, age, trauma, etc. – that justify the exceptionality of the condition, its appearance only in some pregnancies of the same woman, the involvement of the hands and / or feet, the uneven involvement of the different nails.